Head position for better visualization of glottis to improve first-pass intubation: a narrative review - Shrestha, Ashis (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Sniffing position has been suggested to improve the visualization of the glottis during endotracheal intubation however, there are controversies regarding the various position. Therefore, this review is conducted to evaluate the recent evidence. Method: Articles available in google scholar on sniffing position and various other positions for intubation was retrieved. Out of 200 articles published from 2018 to 2022, 14 articles were retrieved for review. Result: The sniffing position was found to be better than the head extension position. However, a few other studies did not give the consistent result to state sniffing position to be better. Head elevation to 5 cm was found to be consistent with aligning the external auditory meatus with the sternal notch. This improved glottis views. This result was also not consistent with all studies. The ramped position was found to be frequently used in obese patients with mixed evidence of benefit. One of the studies reported a modified ramped position in obese females and claimed to have improved laryngeal view. Conclusion: There is inconsistency in evidence, however as there is no evidence of harm, it is wise to use sniffing position for intubation, ramped or modified ramped position for obese patients.